Testıng Holıday Effects On Capıtal Market Performance At The Assocıatıon Of Southeast Asıan Natıons (ASEAN) - Lukman Hakim; Sri Marti Pramudena (Cita Konsultindo Research Center, 2024)
Stock indices in several ASEAN countries such as Indonesia, Thailand, Singapore, Vietnam, the Philippines and Malaysia fluctuated during the holiday period. This shows the volatility of stock performance in the capital market which is thought to be influenced by the holiday effect. Within the observation time or event window 5 days before and 5 days after, the Holiday effect is one of the phenomena where economic and social activities experience changes during the holiday period. The analysis method used descriptive statistical analysis, Kolmogorov Smirnov and Shapiro-Wilk test normality test followed by hypothesis test using Paired Sample t-test and non-parametic Wilcoxon Signed Ranks Test. Indonesia (JCI), Vietnam (VNI), Thailand (SETI), Singapore (STI), Philippines (PSEi) had no difference between before and after holidays during the study year (2018–2022) and Malaysia (KLCI) had differences between before and after holidays during the study year (2018–2022). For further researchers, it is recommended to test for other efficient market anomalies in addition to calendar anomalies and Need to conduct further research by taking longer research time, in order to determine the effect of holidays on capital market performance, especially in ASEAN.